Examining the Strengths and Limitations of Ethnographic Research: An Evaluation of Two Studies in Distinctive Educational Contexts - Natalie-Jane Howard (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2021)
Ethnography offers a holistic approach to qualitative researchers in educational contexts and appeals to scholars who wish seek to reveal rich narratives through their immersion in specific domains. This review paper examines the mobilization of the ethnographic research approach reported in studies from two distinctive learning contexts: an elementary school and a vocational college. Employing the specific evaluative criteria of Punch (2005), the desk-based study draws on existing literature to document the strengths and limitations of ethnographic method and reportage to reveal edifying insights to novice and experienced qualitative researchers who may be contemplating an ethnographic study in the future. The review reveals how extensive ethnography lends itself well to presenting thick descriptions in rich narratives to demonstrate high veracity. In contrast, this research approach may be limited in its verisimilitude, especially if ethnographers abridge their methodological and analytical descriptions and fail to acknowledge reactivity